THE ROLE OF WOMEN IN THE POTTERY BUSINESS TO IMPROVE THE FAMILY ECONOMY IN EAST MASBAGIK VILLAGE - Septian Hari Putra (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2023)
This article examines the role of women in the pottery business in East Masbagik Village. The main issue studied is the extent to which this role can help improve their family's economy. The author uses descriptive qualitative research techniques to interpret and describe data related to the current situation, attitudes and views that occur in society, the conflict between two or more situations, the relationship between variables, differences between facts, the influence on a condition. After going through a series of scientific research, the author found that the role of housewives in improving the economy of their husbands is very helpful in terms of selling the pottery that housewives make which can ease household finances, because the average income of the husbands of mothers who make pottery is not enough to cover expenses. everyday, and never forget her main task, namely as a housewife who takes care of her husband and the needs of their children. The Islamic review of mothers who make pottery craftsmen helping their husbands to earn a living is recommended by Islam because it is stated in the Qur'an and Hadith, besides that permission is obtained from each husband as long as it does not violate Islamic law, for example not open your private parts and avoid buying and selling that smells of usury.